PENGARUH KONSENTRASI CaCl2 DAN LAMA PERENDAMAN TERHADAP SIFAT ORGANOLEPTIK KERIPIK PISANG MULI (Musa paradisiaca L.) DENGAN PENGGORENGAN VAKUM (VACUUM FRYING) - Nurainy, Fibra; Nurdjanah, Siti; Nawansih, Otik; Hidayat, Rahmad (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
The ripe muli banana is very sensitive to high temperatures, therefore this type banana cannot be fried at normal atmosphere pressur. Therefore , a frying process at low temperature and low pressureis needed. The objective of this research was to determine the best CaCl2 concentration, soaking time, and the interaction between  them in producing the best muli banana cracker using vacuum frying. The factorial experiment was arranged  in a complete randomized block design with three replications. The first factor was the CaCl2 (K) concentration and the second factor was soaking time (T). The CaCl2 concentration consisted of three levels: 1% (K1), 2% (K2), and 3% (K3). The soaking times were 10 minutes (T1), 20 minutes (T2), and 30 minutes (T3). Weight of each sample processed was 2 kg. The sensory evaluation data homogeneity  and additivity were  tested using Bartlet  and Tuckey tests.  Then the data were analyzed using ANOVA, and further analyzed using honest significant difference with significant level of 5%. The best organoleptic properties of vacuum fried muli banana cracker was found on the treatment of  1% CaCl2 soaked for10 minutes (K1L1) with characteristics of typical banana aroma, yellow brownish color, sweet and a little bit sour taste, no after taste, and crunchy. The overall acceptance was favorable. Keywords: CaCl2, cracker, crunchiness, muli banana, vacuum frying